An IGC Study of the Role of Washing Procedures on the Adsorption Properties of Activated Carbons - Eva Díaz; Salvador Ordóñez; Aurelio Vega (Adsorption Science & Technology)
Inverse gas chromatography (IGC) was used to study the influence of different washing treatments (acid, basic and combined washings) on the adsorption properties of two different activated carbons (steam- and chemically-activated). Chemical and textural characterization was carried out by the use of nitrogen adsorption, ICP-MS and temperature programmed desorption methods. The adsorption capacity and the interaction strength (sub-divided into dispersive and specific components) were determined by IGC. Washing procedures (especially those involving acid washing) removed mineral ash almost completely from the carbon samples studied. The steam-activated carbon exhibited the best adsorptive behaviour. The removal of mineral ash enhanced the adsorption of the compounds studied, especially alkanes. Washing procedures also modified the chemical structures of the organic functionalities, but this did not appear to be relevant as far as the adsorption properties of these materials were concerned.